PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL DALAM PROSPEKTUS IPO - Latifatun Nafisah; Wahyu Meiranto (Diponegoro Journal of Accounting, 2017)
This study aims to empirically examine the effect of firm characteristics (industrial sector, firm age, retained ownership, firm size, and year when the firm went public) on intellectual capital information disclosure in IPO prospectuses. The study replicate previous research done by Alcaniz et al. (2015). The sample consists of 169 companies listed on Indonesia Stock that going public between 2007-2015. The extent of IC disclosure is collected and measured by using the IC disclosure index and framework proposed by Alcaniz et al. The mutiple regression analysis is used to examine the associations of five potential explanatory variables with intellectual capital disclosure level. The results provide evidence that industrial sector, firm size and year when the firm went public significantly influence IC disclosure in an IPO prospectus. The high-tech companies, larger companies, and those whose went public after 2009 provide more information about IC in IPO prospectuses. The other variables, age and retained ownership, were not significant.